Deciphering the Active Compounds and Mechanisms of HSBDF for Treating ALI via Integrating Chemical Bioinformatics Analysis - Wang, Yanru; Jin, Xiaojie; Fan, Qin; Li, Chenghao; Zhang, Min; Wang, Yongfeng; Wu, Qingfeng; Li, Jiawei; Liu, Xiuzhu; Wang, Siyu; Wang, Yu; Li, Ling; et al. (Frontiers in Pharmacology, 2022)
The Huashi Baidu Formula (HSBDF), a key Chinese medical drug, has a remarkable clinical efficacy in treating acute lung injury (ALI), and it has been officially approved by the National Medical Products Administration of China for drug clinical trials. Nevertheless, the regulated mechanisms of HSBDF and its active compounds in plasma against ALI were rarely studied. Based on these considerations, the key anti-inflammatory compounds of HSBDF were screened by molecular docking and binding free energy. The key compounds were further identified in plasma by LC/MS. Network pharmacology was employed to identify the potential regulatory mechanism of the key compounds in plasma. Next, the network pharmacological prediction was validated by a series of experimental assays, including CCK-8, EdU staining, test of TNF-α, IL-6, MDA, and T-SOD, and flow cytometry, to identify active compounds. Molecular dynamic simulation and binding interaction patterns were used to evaluate the stability and affinity between active compounds and target. Finally, the active compounds were subjected to predict pharmacokinetic properties. Molecular docking revealed that HSBDF had potential effects of inhibiting inflammation by acting on IL-6R and TNF-α. Piceatannol, emodin, aloe-emodin, rhein, physcion, luteolin, and quercetin were key compounds that may ameliorate ALI, and among which, there were five compounds (emodin, aloe-emodin, rhein, luteolin, and quercetin) in plasma. Network pharmacology results suggested that five key compounds in plasma likely inhibited ALI by regulating inflammation and oxidative damage. Test performed in vitro suggested that HSBDF (0.03125 mg/ml), quercetin (1.5625 μM), emodin (3.125 μM), and rhein (1.5625 μM) have anti-inflammatory function against oxidative damage and decrease apoptosis in an inflammatory environment by LPS-stimulation. In addition, active compounds (quercetin, emodin, and rhein) had good development prospects, fine affinity, and stable conformations with the target protein. In summary, this study suggested that HSBDF and its key active components in plasma (quercetin, emodin, and rhein) can decrease levels of pro-inflammatory factors (IL-6 and TNF-α), decrease expression of MDA, increase expression of T-SOD, and decrease cell apoptosis in an inflammatory environment. These data suggest that HSBDF has significant effect on anti-inflammation and anti-oxidative stress and also can decrease cell apoptosis in treating ALI. These findings provided an important strategy for developing new agents and facilitated clinical use of HSBDF against ALI.